Fabry Disease Practice Guidelines: Recommendations of the National Society of Genetic Counselors. Issue 5 (17th July 2013) - Laney, Dawn A.; Bennett, Robin L.; Clarke, Virginia; Fox, Angela; Hopkin, Robert J.; Johnson, Jack; O'Rourke, Erin; Sims, Katherine; Walter, Gerald
Abstract: Identification and comprehensive care of individuals who have Fabry disease (FD) requires a multidisciplinary approach inclusive of genetic testing, test interpretation, genetic counseling, long term disease symptom monitoring, treatment recommendations, and coordination of therapy. The purpose of this document is to provide health care professionals with guidelines for testing, care coordination, identification of psychosocial issues, and to facilitate a better understanding of disease treatment expert recommendations for patients with Fabry disease. These recommendations are the opinions of a multicenter working group of genetic counselors, medical geneticists, and other health professionals with expertise in Fabry disease counseling, as well as representatives/founders of the two United States based Fabry disease patient advocacy groups who are themselves affected by Fabry disease. The recommendations are U.S. Preventive Task Force Class III, and they are based on clinical experience, a review of pertinent English‐language articles, and reports of expert committees. This document reviews the genetics of Fabry disease, the indications for genetic testing, interpretation of results, psychosocial considerations, and references to professional and patient resources.